FORMATION OF PREPARATION OF FUTURE PRIMARY SCHOOL TEACHERS FOR PROFESSIONAL-PEDAGOGICAL COMMUNICATION - Nishanov Mahmud Sobirovich; Alimkulova Ranokhon Gulmirzayevna (Galaxy International Interdisciplinary Research Journal, 2022)
Today, the whole society is undergoing a complex process of reform, including modern higher education. This is reflected in the constant search for the most effective forms and methods of educational work that meet the growing demands of today, improving the content of education, optimizing organizational structures, training specialists in the field of education. Today, not only educators with a certain set of knowledge, skills and abilities, but also a rich inner potential with many features and qualities are required.